Clones from the human gene complex coding for salivary proline-rich proteins. - Azen, E (1984)
The salivary protein gene complex consists of a series of loci coding for related but distinct proline-rich proteins (PRPs) found chiefly in saliva. We have screened a library of human genomic DNA fragments in bacteriophage lambda Charon 4A with a PRP cDNA synthesized and cloned from rat parotid gland mRNA. Two phages (PRP1 and PRP2) hybridizing to the rat probe under moderately stringent conditions contain related but not identical DNAs. Preliminary nucleotide sequence data indicate that both DNAs include regions comprised of nearly identical tandemly repeated sequences, each able to code for about 21 amino acids. The decoded consensus repeat sequence is homologous to the repeating amino acid units found by others in human PRPs. This and other features demonstrate that these two clones are members of the PRP gene family. Polymorphic differences between the DNAs of different individuals were observed after probing digests of human genomic DNA with a HinfI fragment from PRP1. These DNA polymorphisms reflect size differences, possibly caused by frequent unequal crossing-over between the repeated units in the PRP genes.